PEMBERDAYAAN MORAL TERINTEGRASI DALAM PEMBELAJARAN BAHASA INDONESIA - Try Nur Hasanah (Basastra, 2012)
Abstract Moral is something which is interconnected with the ability in determining correct or incorrectness the behavior. It can be looked from someone’s action and language. In order to have moral, someone has to get the language skill. The enableness of moral can be integrated trough Indonesian lesson either through the literature or scientific lesson. The literature always correlate with the student’s life skill in the society, social, the ability in problem solving, the ability in critical thinking, the ability in communicating, having self awareness, the ability in avoiding stress, the ability in making decision, vocational ability, and having the positive behavior. In Indonesian lesson, the students are also taught for have the ability in scientific thinking. That is think systematically and regularly. Directly, the student’s moral is constructed to the positive direction along the expanding of their knowledge and attitude in with learning Indonesian.   Keywords: moral, Indonesian lesson